Analisis Total Bakteri Coliform di Perairan Pantai Liang Kabupaten Maluku Tengah - Sirajuddin, Nur Tasmiah; Mamesah, Juliaeta A. B. (Biocaster : Jurnal Kajian Biologi, 2026)
Coastal waters are widely used for various human activities, including tourism. Liang Beach in Central Maluku Regency is one of the coastal tourist destinations experiencing environmental pressure due to increased population activity that has the potential to cause nutrient enrichment that can increase the number of coliform bacteria as an indicator of microbiological pollution. This study aims to analyze the number of coliform bacteria in the waters of Liang Beach and compare it with the applicable water quality threshold. This study used a purposive sampling method divided into 3 sampling points with 3 replications each, the distance of each point from the coastline is 5 meters, 7 meters, and 10 meters. Analysis of the number of coliform bacteria was carried out using standard microbiological methods and expressed in units of CFU/100 ml. The results showed that the average total coliform bacteria at point 1 was 100 CFU/100 ml, point 2 was 128.7 CFU/100 ml, and point 3 was 94.7 CFU/100 ml. These results indicate that Liang Beach still meets microbiological quality standards and is relatively safe for tourism activities. This research is expected to provide baseline data for microbiological research and sustainable management in the waters of Liang Beach.